Reform of the brazilian RGPS pensions system - Bello, Filipe de Oliveira (2021)
In the last thirty years, the Old-Age Dependency Ratio increased nearly seven points in Brazil, from 7.0 in 1990 to 13.8 in 2020. Projections estimate it will rise to 36.2 in 2050. Furthermore, the condition of the Brazilian public finance is very serious: in 2019 and for the sixth consecutive year, it was in a deficit. The imbalance was mainly caused by social security, in particular by the RGPS (Regime Geral de Previdência Social) pensions system. A reform was approved and started to be implemented this same year, but doubts persist about it being deep enough to guarantee the looked-for equilibrium. Given this situation, the purpose of our work is to provide new insights on the very long run survival of the Brazilian public pensions, under alternative change scenarios, for instance, the shift to a Defined Contribution system. Transition costs and the costs related to the existing minimum guaranteed pension, are accounted for. Findings prove that the reform started in 2019 will decrease the large deficit for the next ten years, but after this an increase will be observed, although smaller than the one in a pre-2019 reform setting. Therefore, the sustainability of the system will remain a critical issue and further and more effective actions will have to be put into practice as soon as possible.